Entropy Squeezing of a Three-Level Atom Interacting with a Cavity Field (Journal of Atomic and Molecular Sciences, 2018)
We study the field entropy squeezing as a measure of the entanglement ina three-level system interacting with a cavity field. Numerical calculations under currentexperimental conditions are performed and it is found that the initial state settingand atom-field coupling present changes of the general features of the field entropysqueezing dramatically.
Keywords: entropy squeezing; three-level atom; entanglement.